L’outillage des étudiants et des nouveaux professionnels : un levier essentiel à l’amélioration des services de santé en français - Bouchard, Pier; Vézina, Sylvain; Paulin, Christine; Provencher, Michele (Université de Moncton et Consortium national de formation en santé, 2009)
Lors de l’évaluation formative du CNFS réalisée en 2006, l’évaluateur a soumis une recommandation entre autres, qui touchait particulièrement la formation des étudiants. Cette recommandation était libellée comme suit : analyser la problématique de l’outillage des étudiants leur permettant de faire face au défi de l’offre active des services de santé en français dans les établissements de santé et développer une stratégie visant à transmettre la compréhension des enjeux et les aptitudes et les habiletés requises pour faire face à ce défi. Pour adresser cette problématique, le CNFS a mandaté une équipe de chercheurs de l’Université de Moncton. Ce rapport ce veut donc la première étape de ce projet et offre un portrait de l’état de sensibilisation des étudiants et diplômés sur les enjeux, les aptitudes et les habilités requises pour faire face à l’offre de services de santé de qualité en français.

Qui sont les étudiantes du programme de formation francophone d’infirmières praticiennes? - Caty, Suzanne; Michel, Isabelle; Pong, Raymond; Stewart, Dianne (Ref;ets, 2007)

Educating Future Physicians for a Minority Population: A French-language Stream at the University of Ottawa - Drouin, Jeanne; Jean, Pierre (Academic Medicine, 2002)
Abstract The Faculty of Medicine at the University of Ottawa has recently developed a French-language undergraduate medical education stream in order to train physicians for the francophone minority population of the province of Ontario. This new program was planned with the following societal requirements in mind: the need to receive health care in one's mother tongue, the need to have physicians who know the community, and the expectation of receiving good medical care in an ambulatory setting. A systematic educational planning model was used in order to develop three educational innovations in response to these needs and expectations: a communication skills laboratory; early student exposure to the ambulatory, primary care setting for development of clinical skills; and clerkship rotations in a francophone community hospital. Program developers provided ongoing faculty development activities in order to prepare francophone faculty for their new roles. They also considered student participation in program development an essential element of its success. The program has positive outcomes both within and outside the Faculty of Medicine. These include an enrichment effect on the English-language stream, an increased interest in medical education, student satisfaction with their community hospital clerkship rotations, and the recognition of the educational program as a national resource for francophone minority groups. Medical schools that serve minority population groups may benefit from the experience gained at the University of Ottawa.

Training medical students to communicate with a linguistic minority group - Drouin, Jeanne; Rivet, Christine (Academic Medicine, 2003)
Effective communication is central to a successful physician–patient relationship. Communication is usually enhanced when the linguistic and cultural attributes of patients are incorporated in health care delivery. With this purpose in mind, the Faculty of Medicine at the University of Ottawa has developed a French-language stream to train future physicians for the francophone minority population of Ontario. As part of this project, a communication skills laboratory was created for francophone students in 1996, since all three tertiary care teaching hospitals operated in English only. The laboratory consists of a controlled environment where francophone students conduct interviews in French while being observed by clinicians trained in observation and feedback techniques. It makes use of simulated patients trained to play specific roles and to give feedback to students. Laboratory sessions take place throughout the first and second years and expose students to 15 scenarios covering different themes in each year. Each scenario includes a communication problem. Facilities are in place for filming the encounters for review by students. The project has had favorable outcomes. Both students and clinician–supervisors find that the laboratory offers an excellent learning environment and describe the cases as realistic and instructive. Clerkship preceptors are pleased with the students' communication skills. Because of the success of the laboratory, faculty authorities plan to translate the scenarios and offer similar sessions to students in the English-language stream. The teaching methods used in the communication skills laboratory may be of interest to other medical schools that serve linguistic minority populations.

Le rôle de l’hôpital communautaire Montfort comme pilier francophone de formation - Joanisse, Dr. John (Reflets, 2002)

Rapport de l’évaluation sommative du Projet de formation et de recherche du Consortium national de formation en santé - LeBlanc, Pierre (Conseillers en gestion PRAXIS, 2008)